1996
DOI: 10.1006/viro.1996.0392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the EBNA1 Proteins of Epstein–Barr Virus and Herpesvirus Papio in Sequence and Function

Abstract: The EBNA1 protein of Epstein-Barr virus (EBV) supports replication and maintenance of the circularized viral chromosome in cells that are latently infected. We have isolated, sequenced, and functionally characterized the EBNA1 gene of herpesvirus papio (HVP), an EBV-like virus that infects baboons. The amino acid sequences of EBNA1 of HVP and EBV are 56% identical, if the difference in the length of the glycine and alanine containing repetitive region, which is much shorter for HVP EBNA1, is omitted for the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 2 publications
1
51
0
Order By: Relevance
“…S2 in the supplemental material) (48). It was determined previously that EBNA1 of EBV can maintain CeHV-12 plasmid replicons (containing CeHV's oriP) and, conversely, that the EBNA1 homologue of CeHV-12 can maintain EBV plasmid replicons, with preference for their homologous oriP sequences (21,39,56). In CeHV-15, site III was predicted, consistent with a previous report (44).…”
Section: Vol 83 2009supporting
confidence: 87%
“…S2 in the supplemental material) (48). It was determined previously that EBNA1 of EBV can maintain CeHV-12 plasmid replicons (containing CeHV's oriP) and, conversely, that the EBNA1 homologue of CeHV-12 can maintain EBV plasmid replicons, with preference for their homologous oriP sequences (21,39,56). In CeHV-15, site III was predicted, consistent with a previous report (44).…”
Section: Vol 83 2009supporting
confidence: 87%
“…Although the ability of FR-bound EBNA1 to activate transcription from EBV and heterologous promoters is well documented (34,35,43), the mechanism underlying this ability is as yet unclear. Studies with EBNA1 derivatives have revealed that a fusion of LR1 to the DBD activates transcription comparably to wild-type EBNA1 (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their biological similarities, the EBV and herpesvirus papio (HVP) genomes exhbit a homologous, colinear organization, and most HVP latent genes have now been cloned (10,11,18,36,42,57; B. Zhao, R. Dalbiès-Tran, and C. E. Sample, manuscript in preparation). The global picture emerging from these reports is that, despite a significant overall divergence in the sequence, many elements important for the function of EBV proteins are conserved in their HVP counterparts.…”
mentioning
confidence: 99%